Barriers and facilitators for strengthening physiotherapy services in Nepal: perspectives from physiotherapists and health providers - Nishchal Ratna Shakya; Amanda Emén; Gillian Webb; Hellen Myezwa; Biraj Man Karmacharya; Ann-Katrin Stensdotter (BMC, 2024)
Abstract Background Physiotherapy provides non-invasive and non-pharmaceutical intervention for curative, rehabilitation and preventative purposes. Physiotherapy is also a central provider of health promotion. As the global burden of non-communicable diseases and chronic health conditions is rising, the importance of physiotherapy services increases. Unfortunately, physiotherapy services in low- and middle-income countries (LMICs) are generally unsatisfactory. In Nepal, the earthquake in 2015 and the COVID pandemic have clearly illuminated the importance of physiotherapy. Objective This qualitative study aimed to identify barriers and facilitators at different system levels for strengthening physiotherapy services in Nepal. Methods Forty semi-structured individual interviews were performed with different health providers. Transcribed interviews were assessed with thematic analysis. A five-level socioecological framework conceptualised multilevel determinants of barriers and facilitators. Results The study revealed various factors that were potential barriers and facilitators across five different levels, namely individual (taking the lead, need for advocacy), interpersonal (lack of recognition and autonomy, networking for referrals and coordination), community (lack of knowledge and awareness, social and family support), organisational (accessibility, workplace and clinical practice, educational opportunities, role of organisations and rehabilitation centres), and public policy level (planning and implementation of policies and programs, medical hegemony, priorities). Government officials, local leaders, and clinicians, half of whom were physiotherapists, agreed on many of the same issues, where a lack of awareness of what physiotherapy is and knowledge about what physiotherapists do was central. Conclusions The results provide information for the development of physiotherapy by pointing out key elements that need attention. Our broad and structured investigation strategy is applicable to others for a comprehensive analysis of barriers and facilitators for physiotherapy services.